2016
DOI: 10.1097/mao.0000000000001172
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Temporal Bone CT Imaging With Respect to Pediatric Bone-anchored Hearing Aid Placement

Abstract: This data shows pediatric temporal bone thickness is frequently greater than the recommended 3 mm, even in patients as young as one. Anatomically, concerns regarding temporal bone thickness in patients younger than five could be reliably addressed with imaging typically obtained in workup of hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…However, a review of temporal bone CT imaging in children aged 1–5.99 years showed the temporal bone thickness to be greater than 3 mm in all age groups, in normal and diseased ears. 2 This is in line with another study where the mean bone thickness lateral to the sinodural angle in the atretic ear in children aged less than six years was at least 4.8 mm, with a thickness of 4.1 mm in the non-atretic ear. 3
A bone-anchored hearing device can be implanted in patients with a chronically discharging ear who are unable to wear conventional hearing aidsPatients need to be aged over one year and have temporal bone thickness of at least 3 mm for device implantationIn patients with thin and irregular skull bone, a computed tomography guided three-dimensional template of the temporal bone can be craftedThis template can help identify an appropriate site for safe bone-anchored hearing device implantation
…”
Section: Discussionsupporting
confidence: 91%
“…However, a review of temporal bone CT imaging in children aged 1–5.99 years showed the temporal bone thickness to be greater than 3 mm in all age groups, in normal and diseased ears. 2 This is in line with another study where the mean bone thickness lateral to the sinodural angle in the atretic ear in children aged less than six years was at least 4.8 mm, with a thickness of 4.1 mm in the non-atretic ear. 3
A bone-anchored hearing device can be implanted in patients with a chronically discharging ear who are unable to wear conventional hearing aidsPatients need to be aged over one year and have temporal bone thickness of at least 3 mm for device implantationIn patients with thin and irregular skull bone, a computed tomography guided three-dimensional template of the temporal bone can be craftedThis template can help identify an appropriate site for safe bone-anchored hearing device implantation
…”
Section: Discussionsupporting
confidence: 91%
“…2). This result is different from the previous study in Caucasians, suggesting that BAHDs should not be routinely applied to patients younger than 5 years of age [11]. Our results are in line with many previous studies showing that skull bone thickness is less than 3 mm in patients younger than 5.…”
Section: Discussionsupporting
confidence: 50%
“…One previous study investigated temporal bone thickness in Caucasians to assess the benefit of BAHD implantation in children younger than 5 years of age. The result of that study showed the average squamous temporal bone thickness was thicker than 3 mm in all age groups, which means that BAHD implantation could be considered for patients younger than 5 years of age [11]. However, no previous studies have investigated BAHD indications with respect to calvarial bone thickness in Korean groups and the present study is the first to establish a safe guideline for Korean groups.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations